2005
DOI: 10.2174/0929866054864319
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Selenocysteine into Proteins Using Peptide Ligation

Abstract: Expressed protein ligation has become a frequently used technique to insert non-standard amino acids into proteins. The technique has been adapted to insert selenocysteine residues in place of cysteine residue in proteins, taking advantage of the similarity in the chemistries of sulfur and selenium. This replacement can confer unique structural and catalytic properties to enzymes and proteins. The development of this technique also allows for naturally occurring selenoproteins to be produced semisynthetically.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 62 publications
1
14
0
1
Order By: Relevance
“…Koppenol and coworkers found that at pH 7, a selenolate catalyzed the reduction of a disulfide *390-fold faster than a thiol. This data is not dissimilar from the data reported in (33) at neutral pH [also see (32)]. The authors noted that the difference in nucleophilicity is significantly decreased, to 10-100-fold, to account for differences in the ionization state of the two chalcogens.…”
supporting
confidence: 67%
“…Koppenol and coworkers found that at pH 7, a selenolate catalyzed the reduction of a disulfide *390-fold faster than a thiol. This data is not dissimilar from the data reported in (33) at neutral pH [also see (32)]. The authors noted that the difference in nucleophilicity is significantly decreased, to 10-100-fold, to account for differences in the ionization state of the two chalcogens.…”
supporting
confidence: 67%
“…Our research efforts over the past several years have focused on synthesizing peptides containing selenocysteine (Sec, U) [1] (Abbreviations used in this paper follow the guidelines recommended by Jones JH) for use in peptide ligation reactions [2,3]. One problem with using Sec in solid-phase peptide synthesis (SPPS) is the requirement for using benzyl-type protecting groups for the selenol side-chain owing to the incompatibility of a trityl group (Trt) with this sidechain [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Scheme 9, the iodination -selenylation protocol was directly applied to lcystine protected with Fmoc groups, 13a, which has a free COOH group. Trapping of the iodide intermediate (18) with the selenolate that was produced by reduction of bis(4-methoxybenzyl) diselenide with NaBH 4 indeed gave the desired product 10 in 12% isolated yield. Although the reaction yield was not remarkably increased compared with the path shown in Scheme 7, the result suggested the compatibility of the S !…”
Section: Synthesis Of Selenocysteinementioning
confidence: 94%